Pengembangan Pembelajaran Pendidikan Agama Islam melalui Pembelajaran Konstruktivistik dan Sosiokultural - Aida Arini; Halida Umami (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2019)
Constructivistic learning is a learning that emphasizes the activity learners and relearning that has been previously possessed. As for the role of teachers in the learning process is as a facilitator who must support the learners in reconstruct the knowledge he has had then associated with new knowledge gained from educators during the process Learning. In sociocultural learning emphasizes more on the interaction between learners and others who will be associated with new knowledge built by educators in the learning process.